Phytochemical Screening of the Ethanol and Aqueous Extracts of Dicliptera verticillata Leaves - , A. E. Akpakpan, E. J. Ukpong, A. O. Odiongenyi, I. E. Willie (Archives of Current Research International, 2017)
Dicliptera verticillata is an underutilized medicinal plant that grows in Akwa Ibom State South-South Nigeria. Ethanol and aqueous extracts of the leaves are sometimes used for the treatment of malaria. The phytochemical compositions of the ethanol and aqueous extract of the leaves were investigated using established analytical procedures. The qualitative phytochemical analysis of the plant extract revealed the presence of alkaloids, saponins, phlobatannins, and deoxy-sugar, in both ethanol and aqueous extracts. Steroids were absent in aqueous extract but present in the ethanol extract while terpenes and cardiac glycoside were absent in the ethanol extract but present in aqueous extract. Anthraquinones and flavonoids were absent in both extracts. The results of this study therefore revealed that the leave extract of Dicliptera verticillata is a good source of phytochemicals that can be harnessed to combat some medicinal issues in the rural communities.